2018
DOI: 10.29252/ijrm.16.5.341
|View full text |Cite
|
Sign up to set email alerts
|

Cervical bacterial colonization in women with preterm premature rupture of membrane and pregnancy outcomes: A cohort study

Abstract: Background:One of the most important etiologies in pretermpremature rupture of membranes (PPROM) is cervical bacterial colonization.Objective:This study evaluated cervical bacterial colonization in women with PPROM and the pregnancy outcomes.Materials and Methods:In this cohort study, 200 pregnant women with PPROM at 27-37 wk of gestation who were admitted in an academic hospital of Mashhad University of Medical Sciences from March 2015 to July 2016 were studied. samples were obtained from endocervical canal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…The majority of E. coli strains were isolated from women with occasional infection, in relation to recurrent and chronic infection (Table 4). Persistent vaginal colonisation by E. coli is a significant risk factor for acute cystitis, recurrent urinary tract infections [24], and premature rupture of membranes, which lead to preterm labour [25]. The frequency of E. coli strains (95.2%) in the study sample was higher than that found in other countries [26,27].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The majority of E. coli strains were isolated from women with occasional infection, in relation to recurrent and chronic infection (Table 4). Persistent vaginal colonisation by E. coli is a significant risk factor for acute cystitis, recurrent urinary tract infections [24], and premature rupture of membranes, which lead to preterm labour [25]. The frequency of E. coli strains (95.2%) in the study sample was higher than that found in other countries [26,27].…”
Section: Discussionmentioning
confidence: 64%
“…While our strategy to group the strains was sound and systematic, the large diversity of the strains prevented an obvious clustering of biological or clinical characteristics. There are relatively few reports in the literature that characterize CVEC strains, and they report a variable level of heterogeneity, and a lack of association with clinical variables [5,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…PROM that occurs prior to 37 weeks of pregnancy is pre-premature rupture of fetal membranes (PPROM) and PROM that occurs after 37 weeks of pregnancy is term-premature rupture of fetal membranes (TPROM). The pathogenesis of TPROM is still unclear, but it usually results from vaginal flora, fallopian tube inflammation, insufficient trophoblastic infiltration, and the abnormal pressure of the amniotic cavity are possible causes of TPROM [4]. At present, clinical prediction of PROM is still difficult to achieve and the effect of traditional single conservative treatment strategies is not satisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…A study in Europe documented a similar prevalence of E. coli of 14 % in cervical samples of women in PTL [ 32 ]. On the other hand, endocervical colonization rates were lower at 3.5 % among women in labor in Switzerland [ 33 ] and higher at 24 % in Iranian women with premature preterm rupture of membranes ROM [ 34 ]. Our pilot study provides initial information on the prevalence of E. coli cervical colonization in US women in PTL.…”
Section: Discussionmentioning
confidence: 99%